2024 Clinical practice guidelines for Acute coronary syndrome without ST segment elevation electrocardiogram - O. V. Averkov; G. K. Harutyunyan; D. V. Duplyakov; E. V. Konstantinova; N. N. Nikulina; R. M. Shakhnovich; I. S. Yavelov; A. N. Yakovlev; S. A. Abugov; B. G. Alekyan; D. M. Aronov; M. V. Arkhipov; et al. (Российский кардиологический журнал)
Russian Society of Cardiology (RSC)With the participation of: the Association of Cardiovascular Surgeons, the Russian Society of Emergency Medical Care, the Russian Association of Ultrasound Diagnostics Specialists in Medicine (RASUDM)Approved by the Research and Practical Council of the Ministry of Health of the Russian Federation